Pengaruh Sponsorship dan Brand Ambassador terhadap Purchase Intention dengan Brand Image sebagai Variabel Intervening: Shopee sebagai Sponsor Utama Liga 1 Indonesia dan Cristiano Ronaldo sebagai Brand Ambassador - Diza Nur Alinda; Herman; Febrina Hambalah (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2022)
This study aims to determine the effect of sponsorship and brand ambassador on purchase intention with brand image as an intervening variable at Shopee as the Main Sponsor of Liga 1 Indonesia and Cristiano Ronaldo as a Brand Ambassador. The method used in this research is quantitative research with explanatory research type. The research was conducted on residents of eastern Surabaya with the criteria that they have never purchased Shopee, know the Shopee League 1 football match, and know Cristano Ronaldo as Shopee's Brand Ambassador with a total of 90 research respondents. The sampling technique for nonprobability sampling was purposive sampling technique and used sample size guidelines according to Hair et al (2014). The data collection technique used a questionnaire using the Structural Equation Modeling (SEM) data analysis technique with the student version of the SmartPLS 3.2.7 analysis tool. The results of this study indicate that: 1. Sponsorship affects Purchase Intention 2. Brand Ambassador does not affect Purchase Intention 3. Sponsorship does not affect Brand Image 4. Brand Ambassador affects Brand Image 5. Brand Image affects Purchase Intention. 6. Brand Image as an integration variable does not indirectly affect the relationship of Sponsorship and Purchase Intention 7. Brand Image as an integration variable indirectly affects the relationship between Brand Ambassador and Purchase Intention.